Growing of coffee seedlings on different substrates and fertilized with lithothamium (2017)
The coffee seedling production quality is essential to ensure crop development in field. Thus, the objective of this study was to evaluate the effect of two substrates (cattle manure and filter cake) interacting with four levels of organic fertilizer with lithothanmium in coffee seedlings var. Lempira production. A completely randomized experimental design was used with factorial arrangement of treatments 5 x 2, five levels of lithothamnium (0, 1.75, 3.50, 5.25, and 7 kg m-3 of substrate), two substrates (cattle manure and filter cake) and three replicates. The variables evaluated were: plant height, number of leaves, stem diameter, and root length. The treatments produced significant effects on the initial development parameters of the coffee seedlings. The best results in plants grown were obtained in cattle manure substrate with 5.25 kg m-3 of lithothamnium, and decreased with levels higher than 1.75 kg m-3 of lithothanmium in filter cake substrate